Tuberculosis in Jayapura: Human Security Threat in International Relations Perspective - Melyana R Pugu; Mariana E Buiney (Journal of Social and Development Sciences, 2017)
The concept of human security defines the purpose of human to be free from poverty, free from terror and free from disease. This paper aims to provide an overview of the infectious disease, tuberculosis (TB), as one of the threats to human security in the city of Jayapura. The method used to assess this study is qualitative research method that describes and illustrates findings in the form of data and figures about the disease both by elaborating primary data collection through interviews with staffs and patients in government-funded health care as well as through secondary data libraries, books, journals and the Internet. The results from this study depict that from 2013 to 2015 the number of tuberculosis patients who reported themselves and get treatment and medication in Jayapura city through public health centres had both increased and decreased significantly. This is due to several reasons i.e. the presence of doctors in the health centres that handled the cases, the rise of patients’ awareness on the treatments, the availability of drugs for TB patients in clinics and assistance facilitating by USAID in Papua under the auspice of WHO. In the perspective of international relations, the increasing spread of tuberculosis in Jayapura has become the serious threat to human security and this requires crucial intervention of multi-stakeholders including local government through its health department covering the issue of the availability of accessible health centres, doctors and drugs for tuberculosis treatment. This also includes the promotion and raising awareness for local community relating to TB testing and maintaining one’s healthy environment.